Antidepressants, relapse-prevention medications and both combined to reduce alcohol-related hospitalizations in individuals with severe alcohol use disorder - Bach, Patrick; Franck, Johan; Hällgren, Jonas; Widing, Härje; Gissler, Mika; Westman, Jeanette (European archives of psychiatry and clinical neuroscience, 2025)
Data on the comparative usefulness of medications commonly prescribed to individuals with alcohol use disorder (AUD) are scarce. This study compared the association between antidepressants, relapse-preventive AUD medication, both, and neither on the risk of subsequent alcohol-related hospitalization in individuals with severe AUD. This retrospective analysis of Swedish nationwide register data used Cox (primary analysis) and logistic (sensitivity analysis) regression models to assess the associations between medication exposure (antidepressants, AUD medication, both, neither) and risk of subsequent alcohol-related hospitalization. The analysis included data on 14,026 individuals who were admitted to the hospital for severe AUD between 2009 and 2020. Antidepressants were not significantly associated with a lower risk of subsequent alcohol-related hospitalization (hazard ratio [HR] = 0.94, 95% confidence interval [CI] = 0.82-1.08), but AUD medication was (HR = 0.61, 95% CI = 0.54-0.69), as were antidepressants plus AUD medication (HR = 0.63, 95% CI = 0.45-0.87) (reference: exposure to neither). Pairwise comparisons showed that AUD medication was associated with a lower risk of hospitalization than antidepressants (HR = 0.65, 95% CI = 0.54-0.78). Antidepressants alone were associated with a higher risk than antidepressants plus AUD medication (HR = 1.50, 95% CI = 1.05-2.15). The sensitivity analysis confirmed the association between AUD medication and lower hospitalization risk. Antidepressant monotherapy was not associated with a lower risk of subsequent alcohol-related hospitalization, but relapse-preventive medication for AUD was, both alone and in combination with antidepressants. These findings support the use of relapse-preventive medication to reduce hospitalization risk in individuals with severe AUD and raise questions about the benefit of antidepressant monotherapy for this purpose.